2005
DOI: 10.1007/s10495-005-0816-4
|View full text |Cite
|
Sign up to set email alerts
|

A novel time resolved fluorometric assay of anoikis using Europium-labelled Annexin V in cultured adherent cells

Abstract: The novel time resolved assay provides the ability to analyse the cell death cascade in adherent cell cultures of the same sample at the same time in a sensitive and reproducible way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
1
8
0
Order By: Relevance
“…Harumi Miyagi et al ( 31 ) observed donor-to-donor variation of the expression of extracellular matrix proteins with different human dental pulp stem cells from deciduous teeth, which could justify the different adhesion behavior between the cultures presented in Figure 6 . This is in agreement with the fact that mesenchymal stem cells, as anchorage-dependent cells, can undergo cell death by the lack of appropriated attachment to a substrate ( 32 ).…”
Section: Resultssupporting
confidence: 87%
“…Harumi Miyagi et al ( 31 ) observed donor-to-donor variation of the expression of extracellular matrix proteins with different human dental pulp stem cells from deciduous teeth, which could justify the different adhesion behavior between the cultures presented in Figure 6 . This is in agreement with the fact that mesenchymal stem cells, as anchorage-dependent cells, can undergo cell death by the lack of appropriated attachment to a substrate ( 32 ).…”
Section: Resultssupporting
confidence: 87%
“…This protocol is optimized for cells in suspension and not for adherent cells. If adherent cells must be used, trypsinization should be avoided or at least minimized if possible to prevent anoikis-induced cell death [28, 29]. Although trypsinization usually does not affect traditional cell death assays (e.g., MTT, XTT assays), it can affect proteins bound to the cellular membrane and change the permeability profile of cells.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 In both cases, the recognition agent is coupled to a second part which can be detected (optical detection, radio labeling, magnetic particles for cell sorting, immunodetection and etc.). 9,10,17,18 Large numbers of the annexin-superfamily proteins are reported to be expressed in eukaryotes. 19 Annexins are widespread, greatly conserved and mostly intracellular proteins that generally are distributed in tissues.…”
Section: Molecular Structure Of Annexin and Detection Of Apoptosismentioning
confidence: 99%